(untitled) (Journal of Computational Mathematics, 1989)
In this paper the results in [5] and [6] related to two-parameter nonlinear problems and computing the folds of degree 3 are generalized to any n-parameter nonlinear problems. Constructing a repeatedly extended system for an n-parameter nonlinear problem we prove that a fold of degree n+1 corresponds to a regular solution of its n-th extended system. Also, the equivalence between the n-th extended system and its reduced system is proved. Finally, some examples are computed.